Radiographic Techniques For Estimating Dental Age: A Comparative Study - Khan, Muhammad Salman; Auerkari, Elza Ibrahim; Suhartono, Antonius Winoto (Riviera Publishing, 2024)
The determination of dental age using radiographic techniques has become a crucial method in forensic dentistry for estimating the chronological age of individuals, particularly in cases involving children and adolescents. This study aims to compare various radiographic techniques in estimating dental age based on tooth development. A comparative research method was employed, analyzing radiographic data from individuals aged 6 to 18 years. The data were collected using two primary techniques: panoramic and intraoral periapical, and analyzed using well-established methods such as the Demirjian and Nolla methods. The results showed that the Demirjian method had a higher accuracy rate compared to other methods, particularly in age estimation for individuals under 12 years old. The discussion highlights that differences in accuracy between techniques are due to better visualization of dental anatomical structures in some techniques. The conclusion of this study is that radiographic methods, especially the panoramic technique and the Demirjian method, are optimal choices for dental age estimation with high accuracy.